Analisis Peran Orangtua Mendampingi Anak Belajar Pada Masa Pandemi Covid-19 Di Kabupaten Jepara - Ahmad Rohman Yusuf; A. Y. Soegeng Ysh; Filia Prima Artharina (STKIP Andi Matappa Pangkep, 2022)
This study aims to describe the implementation and problems that occur in the implementation of good parental learning assistance to elementary school children during the Covid-19 pandemic when learning is carried out from their respective homes. This research method is a qualitative research using data collection techniques in the form of observation, interviews, questionnaires, and documentation. The findings of the research can be concluded that the problem in this research is due to the large number of complaints about the learning assistance process from parents during online learning that is carried out at home during the Covid-19 pandemic, which is very inconvenient for parents. There are several problems experienced by students, one of which is due to parents who are busy working and limited time for mentoring their children's learning. Suggestions from research results that can be conveyed are in the form of solutions when implementing learning assistance carried out by parents when learning is carried out at their respective homes. One of them is if parents are so busy that they are unable to accompany their children in learning, then the parents can provide learning assistance for their children to a tutoring place near their home.